Student Self Efficacy in Wrestling Lectures (Journal of Physical Education Health and Sport, 2022)
The wrestling lecture is one of the courses in the physical education study program, at FKIP, Tanjungpura University. Enthusiasm to take part in wrestling lectures is always shown by almost all students, but some students feel anxious and even afraid to start lectures, especially female students. After undergoing lectures everything changes drastically, students feel anxious, and not confident. This is because students feel surprised and are not ready to take part in wrestling lectures. Poor athlete performance will lead to psychological decline, namely a lack of confidence in one's abilities (self-efficacy). The purpose of this research is to find out the Self Efficacy of students after attending wrestling lectures. This study uses a quantitative method in the form of survey research. The population in this study were students who took wrestling courses in the 2021/2022 semester and the sample consisted of 32 students. The data collection tool is to use a self-efficacy questionnaire. Data analysis uses a quantitative description. The results showed that the number of students who chose the Yes point on the experience indicator of success was 93%, the Other Individual Experience Indicator showed 78%, the Verbal Persuasion Indicator showed all students who chose 100%, the indicator on physiological conditions showed a total percentage of 51%. This study concludes that students believe in themselves with their ability to go through the process and complete the implementation of wrestling lectures with a total percentage of 81%.